Proteomic Profile During Embryonic Development of Dengue Vector Aedes albopictus Mosquito - Rahman, G.M. Saifur; Dieng, Hamady; Ahmad, Abu Hassan; Uyub, Abdul Manaf; M. Rawi, Che Salmah (Oriental Scientific Publishing Company, 2014)
Despite the potential impact of moisture on embryonation and egg eclosion of Aedes mosquitoes, little is known about its effect on protein synthesis during critical embryonic development as well as in the proteomic profiles. Thus, we quantify the protein concentration and proteomic profile during embryonic development of Ae. albopictus from far early of egg laying to egg eclosion in contact with sufficient moisture. It was observed that the concentration of protein started to decrease from the early hours (6th h) with progressing of embryonic development. There were more or less 13 bands observed in Coomassie blue staining of different embryonic stages within the range of ~58 kDa and ~7 kDa by using 12% separating gel in 1D SDS-PAGE. Among them highly expressed bands on the position of 11-13 of lower molecular weight at around 7 kDa were found in all treatments. They may have controlling effects on egg hatching. Identification of these specific proteins can give an insight direction of effective vector control way.